Is Aspirin Still the Cornerstone of Antiplatelet Therapy in Patients With Coronary Artery Disease? An Historical and Practical Narrative Review - Carol Gravinese; Matteo Bianco; Enrico Cerrato; Paola Destefanis; Alessia Luciano; Alessandro Bernardi; Simone Bellucca; Ferdinando Varbella; Fiorenzo Gaita; Roberto Pozzi (Hospital Practices and Research, 2017)
Aspirin is an irreversible and non-selective inhibitor of cyclo-oxygenase. It represents the cornerstone of antiplatelet therapy and is used in secondary prevention of cardiovascular disease. Disagreement over the optimal maintenance dosage still exists; in America and Europe the most used doses of aspirin are 81 mg and 100 mg daily, respectively. There is also debate on the formulation and route of administration of the loading dose. The latest studies advise chewable and non-enteric coated aspirin; intravenous administration represents an alternative for unconscious or shocked patients. Aspirin hypersensitivity is characterized by the onset of respiratory, mucocutaneous, and systemic symptoms. It is marginally considered, but its prevalence is significant. International cardiologic guidelines only report the possibility of desensitizing intolerant patients or, alternatively, administering one single antiplatelet agent. Desensitization can induce a temporary tolerance to the drug and consists of the administration of sequential and incremental doses of aspirin. Rapid desensitization protocols have proven to be safe and effective in the vast majority of cases, and they should be included in the management of these patients. New studies are being carried out comparing aspirin with other antiplatelet agents, and the results will be available shortly.